Invariant Natural Killer T and Mucosal-Associated Invariant T Cells in Asthmatic Patients - Lezmi, Guillaume; Leite-de-Moraes, Maria (Frontiers in Immunology, 2018)
Recent studies have highlighted the heterogeneity of asthma. Distinct patient phenotypes (symptoms, age at onset, atopy, lung function) may result from different pathogenic mechanisms, including airway inflammation, remodeling and immune and metabolic pathways in a specific microbial environment. These features, which define the asthma endotype, may have significant consequences for the development and progression of the disease. Asthma is generally associated with Th2 cells, which produce a panel of cytokines (IL-4, IL-5, IL-13) that act in synergy to drive lung inflammatory responses, mucus secretion, IgE production and fibrosis, causing the characteristic symptoms of asthma. In addition to conventional CD4+ T lymphocytes, other T-cell types can produce Th2 or Th17 cytokines rapidly. Promising candidate cells for studies of the mechanisms underlying the pathophysiology of asthma are unconventional T lymphocytes, such as invariant Natural Killer T (iNKT) and Mucosal-associated invariant T (MAIT) cells. This review provides an overview of our current understanding of the impact of iNKT and MAIT cells on asthmatic inflammation, focusing particularly on pediatric asthma.